The Aggregate Excess Demand Correspondence and the Structure of Economies with Externalities - Scheffman, D. T. (Review of Economic Studies, 1975)
Journal Article The Aggregate Excess Demand Correspondence and the Structure of Economies with Externalities Get access D. T. Scheffman D. T. Scheffman University of Western Ontario Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 42, Issue 4, October 1975, Pages 597–604, https://doi.org/10.2307/2296796 Published: 01 October 1975